Unity for the defence of our rights, of our children, of peace. Special information bulletin. Publ. by the Women's International Democratic Federation (W.I.D.F.). . Strengthen unity in defence of our rights, our children and peace
French ed.: Union pour la défence de nos droits, de nos enfants, de la paix (ZO 32056). - German ed.: Gemeinsame Verteidigung unserer Rechte, unserer Kinder, des Friedes (ZO 32101). - Spanish ed.: Unión para defender nuestros derechos, nuestros hijos, la paz (ZO 32055).